2015
DOI: 10.5194/asr-12-187-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of regional and global reanalysis near-surface winds with station observations over Germany

Abstract: Abstract. Reanalysis near-surface wind fields from multiple reanalyses are potentially an important information source for wind energy applications. Inter-comparing reanalyses via employing independent observations can help to guide users to useful spatio-temporal scales. Here we compare the statistical properties of wind speeds observed at 210 traditional meteorological stations over Germany with the reanalyses' near-surface fields, confining the analysis to the recent years (2007 to 2010). In this period, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
(15 reference statements)
3
27
2
1
Order By: Relevance
“…A comparison with actual wind speed mast measurements at relevant heights that demonstrates the suitability for the case study in this paper can be found in [15]. Moreover, daily and monthly average wind speeds are compared with wind mast measurements in [16] and general improvements to present reanalysis models, namely ERA-Interim and ERA-20C, are found. The spatial resolution is 0.055 • or 6 km and the temporal resolution of the model output is one hour or a quarter of an hour.…”
Section: Wind Speed Datamentioning
confidence: 86%
See 1 more Smart Citation
“…A comparison with actual wind speed mast measurements at relevant heights that demonstrates the suitability for the case study in this paper can be found in [15]. Moreover, daily and monthly average wind speeds are compared with wind mast measurements in [16] and general improvements to present reanalysis models, namely ERA-Interim and ERA-20C, are found. The spatial resolution is 0.055 • or 6 km and the temporal resolution of the model output is one hour or a quarter of an hour.…”
Section: Wind Speed Datamentioning
confidence: 86%
“…In general, market values are higher in the borderland of Germany. The low values in the Alps might be explained by low correlations between wind mast measurements and reanalysis model results due to the complex topography as discussed in [16]. Hence, real market factors could be higher in the Alps.…”
Section: Comparison With Observed Market Value Factorsmentioning
confidence: 96%
“…New high-resolution reanalyses like COSMO-REA6 (Bollmeyer et al, 2015) by the Hans-Ertel-Zentrum (HErZ), based on DWD's operational forecast model COnsortium for Small-Scale MOdelling limited-area model (COSMO-LAM; Schättler et al, 2011), will improve the hindcast evaluations and serve as input for RCM runs. In a first comparison, Kaiser-Weiss et al (2015) have already shown advantages over global reanalyses for ground level wind data, especially in coastal and mountainous regions due to the improved spatial (6 × 6 km) and temporal (hourly) resolution. The same might be expected for the evaluation of (extreme) precipitation and derived indices, like R3d and API.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they yield information that assists users in deciding which reanalysis product might be most suitable for their particular application. The CORE-CLIMAX project developed a set of procedures for comparing reanalyses and for comparing reanalyses to assimilated observations and CDRs (Gregow et al 2014b;Kaiser-Weiss et al 2015). To do so, five categories of comparisons were identified: i) descriptive product comparison, ii) comparison with third-party observation-based CDRs, iii) intercomparison between different reanalyses, iv) thematic comparison (i.e., how well can the reanalysis products be applied to understand a particular problem), and v) internal metrics comparison.…”
Section: Reanalysis Feedback Mechanism To Cdr Updates Procedures For mentioning
confidence: 99%